2013
DOI: 10.1002/joc.3651
|View full text |Cite
|
Sign up to set email alerts
|

Using phenology to assess urban heat islands in tropical and temperate regions

Abstract: ABSTRACT:The study of urban phenology is relevant to assess the effects of heat islands and the potential impacts of climate change on plants. Temperature is the main factor regulating plant development in moist/temperate regions. However, plants in tropical cities may respond to additional environmental cues, such as air humidity. We examined whether differences in air temperature and humidity along an urban-rural gradient influenced phenological onset dates of trees in a temperate mid-latitude city (Munich, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
30
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 43 publications
0
30
0
3
Order By: Relevance
“…In addition the partial absence of phenological response to urban heat islands might be related to decreased water vapour pressure (Gazal et al ., ). Other authors (Do et al ., ; Jochner et al ., ) found an influence of air humidity on phenology in tropical environments.…”
Section: Air Humidity Influences Budburstmentioning
confidence: 98%
“…In addition the partial absence of phenological response to urban heat islands might be related to decreased water vapour pressure (Gazal et al ., ). Other authors (Do et al ., ; Jochner et al ., ) found an influence of air humidity on phenology in tropical environments.…”
Section: Air Humidity Influences Budburstmentioning
confidence: 98%
“…We therefore calculated an index describing the degree of urbanization for each site using the proportion of urban land use with predominantly sealed soil (according to CORINE land cover data, EEA, 2010) within a radius of 2 km. A site was classified as "urban" when the index exceeded the value of 0.5 (see also Jochner et al, 2012Jochner et al, , 2013.…”
Section: Statistical Analysesmentioning
confidence: 99%
“…While our analysis is conducted at a plant functional type level (e.g. grass versus trees), previous fieldand plot-based studies have shown that phenological response to temperature varies at the species level (Bradley et al 1999, Chuine 2000, Primack et al 2004, Morin et al 2009, Vitasse et al 2009, Jochner et al 2013. A further complication is that non-native vegetation is common to urban areas and may be associated with earlier greening in the spring and a concomitantly longer GSL R , as discussed in section 3.2 (McKinney 2002, Niinemets and Peñuelas 2008, Shustack et al 2009, Nemec et al 2011.…”
Section: Comparison Between Remotely Sensed and Temperature-based Metmentioning
confidence: 99%